SISTEM PELAYANAN MASYARAKAT PADA KANTOR KEPALA DESA BALAM SEMPURNA BERBASIS WEB - Roni J Simamora; Eva Julia G. Harianja; Lilis Krisnawati Sihotang (Universitas Methodist Indonesia, 2021)
The Village Service describes the identity of the village itself. So far, the service system for making letters at the office of the Village Head of Balam Sempurna, Rokan Hilir Regency uses services in the form of a manual information system, the service is carried out by a Village Secretary. Some of the problems faced by this service system are difficult and slow in the process of submitting proposals for new letters, permits and certificates. Meanwhile, people want friendly, fast and effective service. The self-service system can be used as a solution to provide excellent service to the community. In this self-service system, the public can access services such as taking care of certificates and cover letters for various purposes by entering or typing the Population Identification Number into the website. If the data is found, the community can immediately perform the desired service. The result of the application is in the form of a certificate or permit